Integrating Quranic Framework for Digital Literacy Curriculum in Madrasa - Kurniawan, Redite; Bakar, M. Yunus Abu; Kholis, Nur (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2024)
The growing prevalence of teenagers engaging with the internet poses a multifaceted challenge, demanding a concerted response. With issues ranging from exposure to illicit content to the potential risks of online behavior, adolescents necessitate guidance to navigate the digital realm safely and ethically. The need for a Quranic-based digital literacy curriculum arises from the imperative to provide teenagers with a comprehensive framework for navigating the internet that goes beyond mere technical skills. By framing digital literacy within a Quranic context, students can learn to utilize the internet in a healthy and ethical manner, while also gaining a deeper understanding of their role in society. Throughout the curriculum, students would engage in reflection activities where they connect Quranic teachings to their own digital experiences. This article discusses the development of a Quran-based Digital Literacy Curriculum for students in MTs. Terpadu Ar-Roihan Lawang Malang. The curriculum was developed using the Research and Development method through ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model, and aimed to address the misuse of personal information and content on the internet. The curriculum was designed to provide students with clear learning objectives, guidance on how to navigate digital challenges, and reflection on Quranic verses related to digital literacy. Based on the validation conducted by four qualified assessors specializing in media and curriculum content, the Quran-based digital literacy curriculum has been assessed to be of high quality. The average scores for both the curriculum media (3.75) and curriculum content (3.88) indicate strong performance in both aspects. Moreover, the total average score of 3.82 suggests an overall very good curriculum product. The curriculum also evaluated on students, with positive feedback received from both students and teachers. Both students and teachers noted that the curriculum's focus on real-life scenarios and practical skills made the content highly relevant.  Suggestions for future research include expanding the curriculum to a broader audience, evaluating the effectiveness over a longer period, exploring the integration of technology, and investigating the effectiveness in addressing other digital literacy topics.